Alkali Pre-soaking Effects on Acridity, Colour Parameters and Oxalate Content of Elephant Foot Yam - Kumar, Anuj; Patel, Ashok A; Singh, R. R. B; Desai, K (JOURNAL OF ROOT CROPS, 2014)
Acridity, an itchy sensation felt in mouth and throat, is a major problem felt upon consumption of elephant foot yam. It is believed to be due to the presence of needle-like crystals (raphides) of calcium oxalate. As a means to overcome this problem presoaking of elephant foot yam (Amorphophallus paeoniifolius) in an alkaline solution was studied. The effect of time (1-3 h) and temperature (40-50 °C) of alkali pre-soaking (0.1% sodium hydroxide solution) on sensory acridity, Hunter colour parameters, oxalate and total solids contents of yam was assessed using response surface methodology. Sensory acridity score was not significantly influenced by the soaking treatment, but the pH, oxalate content and colour co-ordinates and solid losses in soak water were significantly influenced. The linear regression models (pâ‰¤ 0.01) were valid for pH, soak water total solids and soluble oxalate content of elephant foot yam, whereas the quadratic model was valid for the total oxalate content (pâ‰¤ 0.01). The soaking time and temperature had a generally darkening effect on yam as indicated by Hunter L*, a*and b* values as well as the whiteness index derived therefrom, the relevant regression equations representing quadratic models for a* value and whiteness index (p â‰¤ 0.01) and linear models for the remaining parameters (pâ‰¤ 0.01).